Comparison and assessment of the setting zone choices by elite male and female volleyball setters in relation to the quality of defence - Sotiropoulos, K.; Barzouka, K.; Tsavdaroglou, S.; Malousaris, G. (Facta Universitatis: Series Physical Education and Sport, 2019)
The aim of this study was the assessment and comparison of the setting zone choices by male and female elite setters, in relation to the quality of the defensive actions which were carried out in Complex II (KII) and III (KIII). A three-member group of coaches assessed the actions of male (M) and female (F) setters and defenders from 20 volleyball games (M=10, F=10) of National Teams competing in the final phase of the World League 2017. The assessment was based on a 5-point rating scale and included actions that composed a set of 2 contacts in KII and KIII. The test of independence for the variables ("setting zones", "defense quality") was carried out using Fisher`s exact test. Following the overall independence test we tested the difference in proportions between genders for each level of the "setting zone" variable. Results showed that in KII the differences in proportions between genders for each level of the "setting zone" variable were found for zone 4 in favor of the male and zones 2 and 6 in favor of the female players. In KIII and under excellent defensive actions the difference in proportions between genders was found in zones 1 and 6 in favor of the males. In conclusion, under suboptimal and optimal conditions, male setters set the ball to zones 4, 6 and 1 more frequently than females, incorporating them into their offensive strategy, while the latter under good conditions preferred setting to zones 2 and 6.